2006
DOI: 10.1152/jn.00610.2005
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Identification of Surfaces as Fields of Force

Abstract: Chib, Vikram S., James L. Patton, Kevin M. Lynch, and Ferdinando A. Mussa-Ivaldi. Haptic identification of surfaces as fields of force. J Neurophysiol 95: 1068 -1077, 2006. First published October 5, 2005 doi:10.1152/jn.00610.2005. The ability to discriminate an object's shape and mechanical properties from touch is one of the most fundamental somatosensory functions. When exploring physical properties of an object, such as stiffness and curvature, humans probe the object's surface and obtain information from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 23 publications
5
36
0
Order By: Relevance
“…The view that adaptation is about canceling kinematic effects of a perturbation, thus that movements return to near baseline (unperturbed) conditions (e.g., a straight line), was recently challenged by Izawa et al (2008). They suggest that motor adaptation is a process of reoptimization, possibly resulting in a different trajectory in the new environment (Chib et al 2006;Izawa et al 2008). Our results support this notion.…”
Section: Discussionsupporting
confidence: 77%
“…The view that adaptation is about canceling kinematic effects of a perturbation, thus that movements return to near baseline (unperturbed) conditions (e.g., a straight line), was recently challenged by Izawa et al (2008). They suggest that motor adaptation is a process of reoptimization, possibly resulting in a different trajectory in the new environment (Chib et al 2006;Izawa et al 2008). Our results support this notion.…”
Section: Discussionsupporting
confidence: 77%
“…With more simulation studies, it can be further shown that when there is no interaction force, the equilibrium reference trajectory and the equilibrium actual trajectory will be identical to the task trajectory. This is similar to the human experiment results observed in [13], where it shows that humans tend to make compensatory movements with small interaction forces, and seek a trade-off between tracking errors and interaction forces in force fields with moderate stiffness. Based on the above observations, the proposed method could be used for force boundary (object surface) exploration and environment identification.…”
Section: B Different Environmentssupporting
confidence: 88%
“…In recent studies, how to obtain an impedance model and a reference trajectory that result in desired interaction performance has attracted much attention. To understand the mechanisms that humans use in physical interactions with environments, neuroscientists have investigated human motor control and adaptation using controlled force fields [11], [12], [13], [14]. It has been shown that the central nervous system (CNS) of humans has an excellent ability to repetitively adjust and tune the motion and impedance of the limb subject to changing environments and uncertain internal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the curvature of a movement, induced by the presence of an obstacle, influences the curvature of the next movement, even when the obstacle has been removed (Jax and Rosenbaum, 2007). Similarly, when learning to move along a curved force channel, participants exhibit force field adaptation against the channel, as well as changes in the planned curvature of the movement (Chib et al, 2006). Finally, usedependent learning can explain why the motor system arrives at seemingly nonoptimal solutions when adapting to novel dynamics in redundant tasks, as observed in experiment 3 (Scheidt et al, 2005;Diedrichsen, 2007).…”
Section: Discussionmentioning
confidence: 99%